Mental Health Outcomes in Perinatal Women During the Remission Phase of COVID-19 in China - Zeng, Xiaoqin; Li, Wengao; Sun, Hengwen; Luo, Xian; Garg, Samradhvi; Liu, Ting; Zhang, Jingying; Zhang, Yongfu (Frontiers in Psychiatry, 2020)
Background: Since the middle of March, the COVID-19 outbreak has been well contained in China. The prevention and control measures for the outbreak have been downgraded to a normalized level. However, until now, the change in level of psychological health amongst perinatal women during the remission phase of the COVID-19 outbreak has not been investigated in China. The aim of this current study was to assess the symptoms of anxiety, depression, insomnia and quality of life (QOL) in perinatal women and to identify potential risk factors associated with these symptoms. Methods: This was a cross-sectional, hospital-based survey conducted between March 25th till June 5th, 2020 in southern China. Convenient sampling method was adopted. Women’s anxiety, depression, insomnia symptoms and QOL was examined through standardized measurements. Multivariate logistic regression and Analysis of Covariance (ANCOVA) was conducted for the same. Results: A total of 625 perinatal women completed the study; of them, 195 women (31.2%, 95%CI=27.56%-34.84%) reported anxiety, 120 (19.2%, 95%CI=16.10%-22.30%) reported depression, and 87 (13.9%, 95%CI=11.20%-16.64%) experienced symptoms of insomnia. Previous adverse experiences during pregnancy was a significant risk factor for anxiety (OR=1.628, 95%CI=1.069-2.480, P=0.023), depression (OR=1.853, 95%CI=1.153-2.977, P=0.011) and insomnia (OR=2.160, 95%CI=1.290-3.616, P=0.003). Participants having infected friends / families / colleagues were more likely to report anxiety (OR=2.195, 95%CI=1.245-3.871, P=0.007) and depression (OR=2.666, 95%CI=1.482-4.794, P=0.001). Those women whose regular check-ups were severely interrupted by the COVID-19 were also more likely to experience symptoms of anxiety (OR=2.935, 95%CI=1.701-5.062, P<0.001) and insomnia (OR=2.195, 95%CI=1.098-4.390, P=0.026). Conclusion: The COVID-19 pandemic does affect the mental health and well being of perinatal women. Increased attention should be paid to women who have infected friends / families / colleagues and those with previous adverse experiences during pregnancy. Coping strategies that relieve psychological stress during the COVID-19 outbreak should be provided to prevent adverse outcomes for women and their infants.